Pendidikan Moral dalam Permainan Tradisional Cublak-Cublak Suweng Perspektif Psikologi dan Islam - Imroatul Ajizah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The traditional game of Cublak-Cublak Suweng is one of Indonesia's cultural heritages, which has valuable cultural meaning. However, a fact shows that most children nowadays prefer to play digital games to traditional games. They are more familiar with some games on their gadget rather than the traditional game, which has more positive effects on children's development. Not only in terms of social development, but also in sensory-motor development and moral development. This article aims to discuss the importance of children playing traditional games as well as examining the process of internalizing moral education contained in the Cublak-Cublak SSuweng gamebased on a psychological and Islamic perspective. Both from a psychological and Islamic perspective are interrelated to one another to form morals and characters who are accustomed to doing good deeds. "This research adopts a literature review method. The findings from the literature were gathered and analyzed through a descriptive-qualitative approach. The results showed that the traditional games of Cublak-Cublak Suweng could be an alternative medium for internalizing moral values​​in children. This traditional game was useful for preserving local wisdom since it contains some elements of movement that can stimulate children’s moral development, such as honesty, discipline, and responsibility, and other positive behaviors.   Keywords: Moral Education, Traditional Game, Cublak-Cublak Suweng